An Integrated Conceptual Model of Destination Branding – Touristmind - Carvalho, Pedro Domingos da Costa (Journal of Tourism Management Research, 2015)
An assessment of the destination image which does not adopt a branding perspective is inevitably reductive, taking into account the competitive context of tourist destinations. Branding is perceived as fundamental to the conceptual development of destination branding, allowing the definition of a conceptual model to assess and monitor the destinations’ performance as brands and the behaviour of tourists as consumers. The aim of this study is to understand the process of formation of destination branding, its dimensions and its interrelationship proposing a new conceptual model, through an integrated perspective which examines brand identity (brand associations), brand image, perceived quality, satisfaction and loyalty, through the development of scales that allow a better understanding and measurement of these constructs. This article aims at contributing to the progress in the conceptualization of the destination branding which is identified as a concept critical to the success of the marketing of tourist destinations.